Application of methods of mathematical modeling for determining of radiation-protective characteristics of polystyrene-metal composite materials - Klepikov, V.F.; Prokhorenko, E.M.; Lytvynenko, V.V.; Zakharchenko, A.A.; Hazhmuradov, M.A. (Вопросы атомной науки и техники, 2016)
Radiation safety features of polystyrene steel composite materials were found by means of mathematical modeling
techniques. We determined the attenuation of the gamma quantum flux passing through a solid protective layer
compared with those attenuation for the bulk protective layer. Change of fractional attenuation of the dose absorbed
by 10 and 50 mm thick composites is calculated. Dependence between protective properties of composite and its
blend composition was studied. Modifications of technical process of composite materials production were performed.
Rotation speed of agitator system was found. It was defined that heating time of polystyrene steel mix is
longer than heating time of polystyrene tungstic one. Degree of mix heating and integrity of thermic field on its surface
was controlled with the help of IR radiometry methods. Рассчитаны радиационно-защитные характеристики полистирол-стальных композиционных материалов.
Дано сравнение эффективности ослабления потока гамма-квантов в случаях сплошного защитного слоя и
защитного слоя, изготовленного в виде шариков диаметром 2 мм. Рассчитано изменение относительного
ослабления поглощѐнной дозы композитами толщиной 10 и 50 мм. Исследована зависимость между защитными свойствами композита и его компонентным составом. Выполнена доработка технологического про-
цесса изготовления композиционных материалов. Найдены скорости вращения системы размешивания.
Установлено, что время нагрева полистирол-стальной смеси больше, чем время нагрева полистиролвольфрамовой. При помощи методов ИК-радиометрии контролировали степень нагрева смеси и однородность теплового поля по еѐ поверхности. Розраховані радіаційно-захисні характеристики полістирол-стальних композиційних матеріалів. Надано порівняння ефективності послаблення потоку гамма-квантів у випадках суцільного захисного шару і захисного шару,
виготовленого у вигляді кульок діаметром 2 мм. Розрахована зміна відносного послаблення поглиненої дози
композитами завтовшки 10 і 50 мм. Досліджена залежність між захисними властивостями композиту і його компонентним складом. Виконано доопрацювання технологічного процесу виготовлення композиційних матеріалів.
Знайдені швидкості обертання системи розмішування. Встановлено, що час нагріву полістирол-сталевої суміші
більший, ніж час нагріву полістирол-вольфрамової суміші. За допомогою методів ІЧ-радіометрії контролювали ступінь нагріву суміші і однорідність теплового поля по її поверхні.